Changing trends in ethnicity and academic performance: observational cohort data from a UK medical school. Issue 12 (15th December 2022) - Mukherji, Prokriti; Adas, Maryam A; Clarke, Benjamin; Galloway, James B; Mulvey, Thomas; Norton, Sam; Turner, Jonathan; Russell, Mark D; Lempp, Heidi; Li, Shuangyu
Abstract : Objective: Quantify differential attainment by ethnicity in undergraduate medical assessments and evaluate whether institutional efforts to reduce the attainment gap have had impact. Design: Observational cohort study. Setting: A single UK MBBS medical programme. Participants: Pseudonymised data of adults aged ≥18 years enrolled in one of the UK MBBS medical programmes between 2012 and 2018. Ethnicity was self-declared during enrolment as White, Asian, Black, mixed and other. Main outcome measure: Module mark (distinction, merit, pass, fail) graded according to a variety of assessments, including single best answer examinations, objective structured clinical examinations and coursework submissions. All modular assessments are graded as a percentage. Logistic regression models were used to calculate relative risk ratio to study the association between ethnicity and attainment gap over a calendar and scholastic year. Models were adjusted for age, gender, social deprivation and scholastic year of study. Results: 3714 student records were included. In the sample, 2134 students (57%) were non-white. The proportion of non-white students increased from 2007 (49%) to 2018 (70%). Mean age was 18 (IQR 18–21) and 56.6% were females. Higher proportion of non-white students 218 (24.8%) were from more deprived backgrounds versus white 76 (14.8%). Compared with non-white, there were no significant differences in the proportion of students failing assessments. However, white students were more likely to achieve merit (relative risk ratio 1.29 (95% CI 1.08 to 1.45)) or distinction (1.69 (95% CI 1.37 to 2.08)). Differences in attainment gap have remained unchanged over time, and for black students, attainment gap grew between their first and final year of study. Conclusion: A similar proportion (97%) of non-white and white students had a passing score, but attainment gap for higher grades persists over years despite widespread efforts in medical schools to diminish the attainment gap linked to ethnicity. Our findings are from a single institution, thus affecting generalisability.